2000
DOI: 10.1161/01.hyp.36.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Blood Pressure and Obesity With the Dopamine D2 Receptor Gene Taq I Polymorphism

Abstract: Abstract-Pharmacological data suggest that obesity and blood pressure (BP) may be modulated through the dopamine D2 receptor (DD2R), which may represent an underlying mechanism that links these conditions. A TaqI polymorphism near the DD2R gene has been associated with indices of obesity in white populations. We compared anthropometric and fasting plasma biochemical parameters between 209 nondiabetic hypertensive and 174 gender-matched normotensive Chinese subjects. The hypertensives had increased dyslipidemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0
4

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 46 publications
4
46
0
4
Order By: Relevance
“…Additionally, Hanson et al [11] found linkage between chromosome 11q and body mass index (BMI) and diabetes mellitus. In a populationbased study, we have previously reported this polymorphism to be associated with both obesity and blood pressure in normoglycaemic Chinese subjects, but in diabetics only the relationship with obesity was evident [12,13]. In this study we report additional data, in a different study group, supporting a relationship between this marker and blood pressure in an affected pedigree member (APM) analysis.…”
Section: Introductionsupporting
confidence: 55%
“…Additionally, Hanson et al [11] found linkage between chromosome 11q and body mass index (BMI) and diabetes mellitus. In a populationbased study, we have previously reported this polymorphism to be associated with both obesity and blood pressure in normoglycaemic Chinese subjects, but in diabetics only the relationship with obesity was evident [12,13]. In this study we report additional data, in a different study group, supporting a relationship between this marker and blood pressure in an affected pedigree member (APM) analysis.…”
Section: Introductionsupporting
confidence: 55%
“…However, these studies have shown mixed results, some have been inconclusive and some have indicated common polymorphisms. [29][30][31][32] For example, a recent study found that peroxisome proliferator-activated receptor gamma 2 polymorphism (Pro12Ala), which is associated with obesity, was also associated with hypertension. 32 Undoubtedly, there will be further studies that consider such common effects and it may be that there are common genes between these phenotypes only under certain contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in obese patients with polymorphism for this allele (Taq1) showed a gynecoid distribution of body fat, without a considerable deviation in arterial tension values. 48 Although this is not a conclusive study, the development of obesity-coexisting AHT is not discarded, because these are relatively young patients which would not have developed AHT yet.…”
Section: Obesity and Hypertensionmentioning
confidence: 99%